Moment-resisting self-drilling dowel connections between steel link beams and CLT for coupled walls. (July 2022) - Moerman, Ben; Li, Minghao; Palermo, Alessandro; Liu, Angela
Abstract: Coupled cross-laminated timber (CLT) walls can be created by connecting steel link beams between adjacent CLT wall panels and are an efficient alternative to conventional cantilevered CLT shear walls. Effective coupling in the coupled wall system requires the beam to wall connections to have adequate strength to ensure a ductile link beam response and adequate stiffness to yield the link beams at relatively low inter-storey drifts. This study evaluates beam to wall connections with a group of self-drilling dowels (SDDs) installed through an 8mm steel knife plate to connect 200UB18 steel link beams to 5-ply CLT walls. A simplified method for determining the connection strength is presented and used to capacity design the test specimens. The capacity design method was validated for the tested specimens because the damage was concentrated in the steel link beams and the connection's peak strength was not exceeded. This study indicates that the SDD connections may be a feasible beam to wall connection solution in coupled CLT wall systems because the capacity protected connections had adequate strength and relatively high stiffness.